Quantitative Correlation at the Molecular Level of Tumor Response to Docetaxel by Multimodal Diffusion-Weighted Magnetic Resonance Imaging and [F]FDG/[F]FLT Positron Emission Tomography - Valerie S. Honndorf; Holger Schmidt; Hans F. Wehrl; Stefan Wiehr; Walter Ehrlichmann; Leticia Quintanilla-Martinez; Hervé Barjat; Sally-Ann Ricketts; Bernd J. Pichler (Molecular Imaging)
We aimed to quantitatively characterize the treatment effects of docetaxel in the HCT116 xenograft mouse model, applying diffusion-weighted magnetic resonance imaging (MRI) and positron emission tomography (PET) using 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) and 3′-deoxy-3′-[ 18 F]-fluorothymidine ([ 18 F]FLT). Mice were imaged at four time points over 8 days. Docetaxel (15 mg/kg) was administered after a baseline scan. Voxel-wise scatterplots of PET and apparent diffusion coefficient (ADC) data of tumor volumes were evaluated with a threshold cluster analysis and compared to histology (GLUT1, GLUT3, Ki67, activated caspase 3a). Compared to the extensive tumor growth observed in the vehicle-treated group (from 0.32 ± 0.21 cm 3 to 0.69 ± 0.40 cm 3 ), the administration of docetaxel led to tumor growth stasis (from 0.32 ± 0.20 cm 3 to 0.45 ± 0.23 cm 3 ). The [ 18 F]FDG/ADC cluster analysis and the evaluation of peak histogram values revealed a significant treatment effect matching histology as opposed to [ 18 F]FLT/ADC. [ 18 F]FLT uptake and the Ki67 index were not in good agreement. Our voxel-based cluster analysis uncovered treatment effects not seen in the separate inspection of PET and MRI data and may be used as an independent analysis tool. [ 18 F]FLT/ADC cluster analysis could still point out the treatment effect; however, [ 18 F]FDG/ADC reflected the histology findings in higher agreement.